2006
DOI: 10.1016/j.ympev.2005.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and historical demography of Atlantic bigeye tuna (Thunnus obesus)

Abstract: analyses dated divergence of Clade I and Clade II during the Pleistocene, as previously proposed. In addition, migration rates were estimated using coalescent methods, and showed a net migration from Atlantic Ocean feeding grounds towards the Gulf of Guinea, the best-known spawning ground of Atlantic bigeye tuna.Running title: Genetic diversity of Atlantic bigeye tuna

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
60
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 44 publications
14
60
1
2
Order By: Relevance
“…Keragaman genetik yang tinggi juga telah dilaporkan oleh beberapa penelitian lainnya diantaranya Moria et al (2009) yang memperoleh keragaman genetik ikan sirip kuning berdasarkan sampel larva sebesar 0,878, Wu et al (2010) keragaman genetik ikan tuna sirip kuning sebesar 0,992 di Barat Samudera Pasifik dan 0,999 di Barat Samudera Hindia, serta Kunal dan Kumar (2013) memperoleh keragaman genetik tuna sirip kuning sebesar 0,998. Hasil penelitian ini, mirip dengan laporan hasil penelitian ikan migratory pelagis lainnya seperti tuna albacore (Thunnus alalunga), tuna mata besar (Thunnus obesus) dan ikan cakalang (Katsuwonus pelamis) (Carlsson et al, 2004;Chiang et al, 2006Chiang et al, , 2008Martinez dan Zardoya, 2005;Martinez et al, 2006;Nugraha, 2009;Dammannaggoda, 2007;Suman et al, 2013). Kemiripan tingkat keragaman genetik tuna merupakan ciri dari ikan dengan tingkat migrasi yang ditinggi, dimana tuna merupakan ikan bermigrasi jauh.…”
Section: Keragaman Genetikunclassified
“…Keragaman genetik yang tinggi juga telah dilaporkan oleh beberapa penelitian lainnya diantaranya Moria et al (2009) yang memperoleh keragaman genetik ikan sirip kuning berdasarkan sampel larva sebesar 0,878, Wu et al (2010) keragaman genetik ikan tuna sirip kuning sebesar 0,992 di Barat Samudera Pasifik dan 0,999 di Barat Samudera Hindia, serta Kunal dan Kumar (2013) memperoleh keragaman genetik tuna sirip kuning sebesar 0,998. Hasil penelitian ini, mirip dengan laporan hasil penelitian ikan migratory pelagis lainnya seperti tuna albacore (Thunnus alalunga), tuna mata besar (Thunnus obesus) dan ikan cakalang (Katsuwonus pelamis) (Carlsson et al, 2004;Chiang et al, 2006Chiang et al, , 2008Martinez dan Zardoya, 2005;Martinez et al, 2006;Nugraha, 2009;Dammannaggoda, 2007;Suman et al, 2013). Kemiripan tingkat keragaman genetik tuna merupakan ciri dari ikan dengan tingkat migrasi yang ditinggi, dimana tuna merupakan ikan bermigrasi jauh.…”
Section: Keragaman Genetikunclassified
“…In other tuna species DNA studies have revealed little intra-specific divergence within, but significant divergence between ocean basins. In bigeye tuna (T. obesus) DNA markers showed no divergence among population samples from the western Pacific Ocean (Chiang et al, 2006), but high divergence among Atlantic and Indo-Pacific populations (Chow et al, 2000;Chiang et al, 2006;Martinez et al, 2006). Similarly, in albacore tuna (T. alalunga) no genetic differences were detected among samples from the Northwest Pacific Ocean (Wu et al, 2009), but significant differences were reported among Atlantic and Indo-Pacific populations (Vinas et al, 2004).…”
Section: Intraspecific Divergencementioning
confidence: 99%
“…In the North Atlantic, marine species (so far investigated) seem to follow a pre-LGM expansion model, e.g., the common goby (Gysels et al 2004), the Atlantic swordfish , the Atlantic bluefin tuna , Atlantic bigeye tuna (Martinez et al 2006), the red alga Palmeria palmata (Provan et al 2005), the brown alga Fucus serratus (Hoarau et al submitted), the bivalve Macoma balthica (Luttikhuizen et al 2003) and the estuarine fish, Ethmalosa fimbriata (Durand et al 2005); where the date of expansion was estimated at between 536,000 (for the common goby) and 128,000 years (for the red alga, Palmeria palmata). Thus, it is likely that highly mobile species and/or those able to shift in the subtidal fared better in the many glacial-interglacial periods.…”
Section: Phylogeographic Patternsmentioning
confidence: 99%